Towards a Critical Framework of Learning in Retirement - Sean Joo Kim (Adult Education Research Conference, 2010)
This paper reviews two retirement models and describes their lack of attention to retirement as an outdated social institution, limiting our understanding of retirement’s features. The need for awareness of retirement insecurity as being embedded in traditional career paths is addressed, and implications for adult education are presented.